Monopsonists, disruptive innovation and food security: The case of high‐value commodity - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod Kumar; Dsouza, Alwin (Agricultural and Applied Economics Association, 2022)
Private firms in monopsony undertake disruptive innovation like contract farming (CF), where the firm invests in the food supply chain, provides credit, assumes the risk, and implements management strategies. This study investigates the impact of monopsonist involvement in CF and its impact on food security indicators among smallholders. Findings reveal that the monopsonist CF structure for ginger processing in Nepal increases the market price by about 18%, yields by 10%, and profits by 66%. However, the impact varies with farm size. Small farms (≤0.51 hectares (ha)) engaged in CF have higher yields (18%), earn higher profits (81%), and receive higher market prices (12%) than small noncontract ginger producers. Contrary to popular belief, disruptive innovation in value chains by monopsonists could lead to higher yields, the market price received, and profitability for both small and large farmers.